Square Wave Pulse Deposition of Gold Nanoparticles for Ethanol EOR Performance and Its Electrochemical Properties Investigation - Mahmud, Amir; Tri Goutomo, Bimo (Pusat Inovasi Sains, 2024)
In this study, gold nanoparticles (Au NPs) were successfully synthesized using square wave pulse deposition. The synthesis process involved applying a lower potential of -0.1 V and an upper potential of 0 V for 25 minutes. Characterization of the synthesized Au NPs was conducted using X-ray diffraction (XRD), scanning electron microscopy (SEM), energy dispersive X-ray (EDX) spectroscopy, electrochemical impedance spectroscopy (EIS), and cyclic voltammetry (CV). The XRD analysis confirmed the formation of the Au phase on the FTO substrate. The SEM images revealed a nanopyramid-like morphology, with an average particle size ranging from 20 to 200 nm. The EIS measurements indicated low resistance values for the Au NPs. During the CV test for ethanol electrooxidation, a stable electric current of 4.28 mA/cm² was achieved, demonstrating good stability in the electrochemical process.